SLANG AS AN EXISTENTIAL FORM OF LANGUAGE: THE DEGREE OF INDEPENDENCE (Proceedings of Southern Federal University. Philology, 2012)
Redkozubova Ye.A.Keywords: slang, autonomous, language, grammar, vocabulary.The article deals with the problem of slang as an autonomous/semiautonomous language system. The author stresses the point that slang should be viewed as a linguistic phenomenon, possessing not only specific lexemes but some grammatical peculiarities as well.